Respiratory Function and Grip Strength in the Acute Phase of Stroke Are Associated with Stroke Severity and Disability at Hospital Discharge - Alvarez Sartor, Lorena Cristina [UNESP]; Luvizutto, Gustavo Jose; Souza, Juli Thomaz de [UNESP]; Silva Dalle Molle, Evelin Roberta [UNESP]; Modolo, Gabriel Pinheiro [UNESP]; Silva, Tais Regina [UNESP]; Prudente, Robson Aparecido [UNESP]; Ribeiro, Priscila Watson [UNESP]; Molle da Costa, Rafael Dalle [UNESP]; Oliveira Antunes, Leticia Claudia de [UNESP]; Ferreira, Natalia Cristina [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; et al. (Hindawi Ltd, 2020)
Introduction. Stroke can lead to musculoskeletal and respiratory dysfunction, chronic deconditioning, and functional limitations, as well as long-term complications. Objective. The aim of this study was to evaluate the association between respiratory function and grip strength in the acute phase of stroke and stroke severity, disability, and autonomy in the long term. Methods. This was a cohort study including 46 patients in the stroke unit. The stroke patients were assessed in the stroke unit at the following moments: at admission by the clinical and haemodynamic stability, demographic and anthropometric data, hand grip strength, stroke severity by National Institutes of Health Stroke Scale (NIHSS) score, and respiratory function using a manovacuometer; during hospitalization by clinical complications and the length of stay; and at hospital discharge and 90 days after discharge by the degrees of functional capacity and dependence using NIHSS, modified Rankin scale (mRs), and Barthel index. Data analysis was performed by multiple linear regression to verify the association between respiratory function and grip strength and the outcomes. Results. The median length of stay in the stroke unit was 7 days. A negative correlation was found between the palmar prehension strength on the unaffected side and mRs at discharge (beta=-0.034, p=0.049). The NIHSS scores at discharge (beta=-0.016, p=0.011) were negatively correlated with the MEP. The Barthel index at discharge was positively correlated with the palmar prehension strength on the unaffected side (beta=0.480, p=0.023). Conclusion. It was concluded that a loss of grip strength is associated with a loss of ability and autonomy at discharge and poor respiratory function is associated with stroke severity at discharge.